2019
DOI: 10.1177/0883073819827407
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Perampanel Oral Suspension in Pediatric Patients From ≥2 to <12 Years of Age With Epilepsy: Pharmacokinetics, Safety, Tolerability, and Efficacy

Abstract: Study 232, an open-label pilot study with an extension phase, evaluated the pharmacokinetics and preliminary safety/tolerability and efficacy of adjunctive perampanel oral suspension (≤0.18 mg/kg/d) in epilepsy patients aged ≥2 to <12 years. Patients were grouped into cohorts 1 (aged ≥7 to <12 years) and 2 (aged ≥2 to <7 years). The Core Study included pretreatment (≤2 weeks) and treatment phases (7-week titration; 4-week maintenance; 4-week follow-up [for those not entering the extension]). The extension phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 13 publications
(34 reference statements)
3
34
1
Order By: Relevance
“…In paediatric patients, two prospective, open-label, multicentre studies had extractable outcome data in generalised seizures: Study 311 (NCT02849626) [ 9 ] and Study 232 (NCT01527006) [ 10 ]. In Study 311, from a population of 180 patients aged 4 to < 12 years with focal seizure or PGTCS, 31 patients had generalised seizures, and among the 22 with PGTCS at baseline, seizure frequency was reduced by a median of 69% (95% CI 18–100; IQR 82) [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In paediatric patients, two prospective, open-label, multicentre studies had extractable outcome data in generalised seizures: Study 311 (NCT02849626) [ 9 ] and Study 232 (NCT01527006) [ 10 ]. In Study 311, from a population of 180 patients aged 4 to < 12 years with focal seizure or PGTCS, 31 patients had generalised seizures, and among the 22 with PGTCS at baseline, seizure frequency was reduced by a median of 69% (95% CI 18–100; IQR 82) [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In study 232, of 50 patients aged ≥ 2 to < 12 years, 22 had generalised seizures, with a median 35.8% reduction in overall seizure frequency and a responder rate of 59.1% in the 11-week core study treatment phase. Seizure data were presented by age subgroups for these 50 patients, but with small numbers and highly variable data (Supplemental Tables S8 and S9, see ESM 1 ) [ 10 ]. Safety outcomes were not reported for the generalised seizure subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…Results from an open‐label pilot study (with long‐term extension; Study 232 [NCT01527006]) of once‐daily adjunctive perampanel oral suspension in patients with epilepsy aged ≥2 to <12 years showed that perampanel PK is independent of age, weight, or liver function. This suggests that the same perampanel dose (mg/day) can be given to adults and children (≥2 years of age) without the need for age or weight‐based adjustments to achieve exposures shown to be efficacious …”
Section: Introductionmentioning
confidence: 99%
“…Perampanel (up to 12 mg/day) demonstrated efficacy and tolerability in randomized, double‐blind, placebo‐controlled phase III studies in patients aged ≥12 years with uncontrolled focal seizures, with or without focal to bilateral tonic‐clonic (FBTC) seizures (previously secondarily generalized seizures), and in patients aged ≥12 years with idiopathic generalized epilepsy and GTC seizures 3‐7 . Perampanel oral suspension (up to 0.18 mg/kg/day) demonstrated efficacy and tolerability in a phase II study of patients aged ≥2 to <12 years with epilepsy 8 . However, there is limited information available on how data from these trials have been adapted to clinical practice in the real‐world epilepsy clinic.…”
Section: Introductionmentioning
confidence: 99%